Effects Of Plyometric Exercises With Repetition Training Method On Vertical Jump Performance And Soccer-heading Skills - Zemam Abderrahman . (sports creativity, 2025)
This study aims to find out ” Effects of Plyometric Exercises with Repetition Training Method on Vertical Jump Performance and Soccer-Heading Skills”. An Experimental Study Conducted on Junior Players, U-17 Khemis M.C. Soccer Team. To achieve this, the sample includes (18) soccer junior players from Khemis M.C. Soccer Team, the players were divided into equated groups ; (09) as a control group and (09) as a experimental group.The experimental group got the suggested plyometric training program whill the control the usual one. pre and post study tests were applied for (09) weeks. all the junior players of the two groups had tests including the vertical jump and Long Distance Ball Heading Test .The (spss) program was used for analyzing data after collecting them.The study indicates that there are statistically significance difference between pre and post measurements for the benefit of the latter related to the experimental group and particularly in all study variables.The researcher has recommendad applying plyometric exercices with repetition training in training process.